Heart Block Initiated by Candlenut Ingestion. (30th May 2022) - Lawani, Osayi; Winter, Mark
Abstract : The candlenut tree is a tropical plant that has a vast number of uses which include fertilizer, dye, ink for tattooing, and fuel. The inner seed of the nut is the most utilized portion of the plant and is often sold as a food additive, natural laxative, or a weight loss supplement. Unfortunately, the seed itself is very toxic when consumed whole and in its raw state. Typical symptoms of toxicity include abdominal pain, vomiting, and diarrhea. Rarely, it can cause cardiac dysrhythmias, most commonly bradycardia and atrioventricular heart block. We present a case of a young adult female with no significant past medical history who developed typical symptoms of toxicity, as well as atrioventricular heart block following ingestion of a candlenut. Most documented cases describe complete resolution of gastrointestinal and cardiac symptoms about one week following ingestion; however, treatment while inpatient can consist of inotropes or vasopressor support, intravenous fluid hydration, electrolyte replacement, and antiemetics. Although the mechanism of action remains unclear, this report provides physicians with an understanding of the risks of ingestion and the knowledge of typical management of the toxic effects of the candlenut.